KEPEMIMPINAN KEPALA DESA DALAM PENGELOLAAN DANA DESA DI DESA PADAS, KECAMATAN KEDUNGJATI, KABUPATEN GROBOGAN - Naufan, Fakkar Dafin; ., Kushandajani (Journal of Politic and Government Studies, 2019)
This research is entitled "Leadership of Village Heads in Management of Village Funds in Padas Village, Kedungjati District, Grobogan Regency". Leadership has an important role in determining the performance of public organizations to manage village funds in accordance with established government regulations. The leadership of the village head is also very important in prioritizing development programs to suit the needs of the local community. This research was conducted in Padas Village because Padas Village was one of the villages that carried out disbursement later than the other villages. This study aims to find the year the cause of this is based on the concept of traditional and transactional leadership of the village head. The leadership of the village head is analyzed based on the role of the village head in general which has been stated in the Law, government regulations, regent regulations concerning the management of village funds.